Following Christ, Not Trends: Christian Ethical Formation for Adolescents in the Digital Age - Rumondor, Mariana Yolanda Y; Mawikere, Marde Christian Stenly; Raintung, Agnes (Peneliti.net, 2025)
The digital era presents Christian adolescents with profound ethical challenges, particularly in relation to identity formation, the pervasive use of social media, and constant exposure to popular cultural narratives that frequently conflict with the values of the Gospel. This study explores the role of Christian ethics as a foundational moral and spiritual framework for guiding young people to remain steadfast in their faith amidst the pressures of digital culture. Employing a descriptive qualitative methodology, this research draws upon an extensive literature review and critical analysis of ten selected academic sources, both national and international in scope. The findings reveal that Christian education—within the contexts of the family, church, and school—plays a pivotal role in nurturing ethical awareness and spiritual resilience among adolescents in today’s digital landscape. Moreover, when accompanied by intentional pastoral care and the active involvement of faith communities, digital platforms, including social media, may be appropriated as constructive instruments for catechesis, character formation, and spiritual growth. This study concludes that Christian ethics must not be understood merely as a set of prescriptive moral norms, but rather as a transformative calling that shapes the character of young believers, cultivates discernment in digital engagement, and deepens their relationship with Christ. In an increasingly digitalised world, such an ethical framework is essential for equipping adolescents to embody and communicate the values of the Gospel with integrity and conviction.